2003
DOI: 10.1074/jbc.m303713200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a cGMP-dependent Pathway in the Natriuretic Peptide-mediated Hormone-sensitive Lipase Phosphorylation in Human Adipocytes

Abstract: Our previous studies have demonstrated that natriuretic peptides (NPs), peptide hormones with natriuretic, diuretic, and vasodilating properties, exert a potent control on the lipolysis in human adipocytes via the activation of the type A guanylyl cyclase receptor (1, 2). In the current study we investigated the intracellular mechanisms involved in the NP-stimulated lipolytic effect in human preadipocytes and adipocytes. We demonstrate that the atrial NP (ANP)-induced lipolysis in human adipocytes was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(173 citation statements)
references
References 49 publications
(28 reference statements)
6
157
1
3
Order By: Relevance
“…This was confirmed using the cGMP analogue inhibitor of cGK-I, 8-pCPT-cGMPS, which inhibited both HSL phosphorylation/activation and lipolysis. 5 This finding in isolated human fat cells confirms early data from a rat cell-free system where the phosphorylation of HSL by PKG was reported. 83,84 Recent studies have shown a role for the MAP-kinases in the control of lipolysis by TNF-␣ in human fat cells.…”
Section: Lipolytic Effect Of Natriuretic Peptidessupporting
confidence: 89%
See 1 more Smart Citation
“…This was confirmed using the cGMP analogue inhibitor of cGK-I, 8-pCPT-cGMPS, which inhibited both HSL phosphorylation/activation and lipolysis. 5 This finding in isolated human fat cells confirms early data from a rat cell-free system where the phosphorylation of HSL by PKG was reported. 83,84 Recent studies have shown a role for the MAP-kinases in the control of lipolysis by TNF-␣ in human fat cells.…”
Section: Lipolytic Effect Of Natriuretic Peptidessupporting
confidence: 89%
“…In contrast, NPs activate a 3Ј, 5Ј-cyclic guanosine monophosphate (cGMP)-dependent pathway that is completely independent from the cAMP-dependent pathway. 5 The NPs may represent a promising new pathway contributing to the control of lipid mobilization in humans in physiological and pathological conditions. The introductory section summarizes the role of circulating NEFAs and the regulation of lipolysis and lipid mobilizing pathways.…”
mentioning
confidence: 99%
“…In our study, simple and multiple regression analyses showed that the HMW adiponectin level correlated with BNP levels. NTproBNP is an inactive surrogate marker of BNP and there is evidence that natriuretic peptides have a direct lipid-mobilizing effect 27,28) . This suggests a causal relationship between BNP and adiponectin; however, further investigations are needed to elucidate a mechanistic link between BNP and adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…The slight decrease in phosphodiesterase 3B mRNA levels observed in the present study could favour an increase in fat cell cAMP levels and thus enhance lipolysis. However, the decreased levels of hormonesensitive lipase and natriuretic peptide type A receptor (which mediates cyclic GMP-dependent activation of lipolysis in human adipocytes [45]) mRNAs indicate a decreased lipolytic capacity. In addition, the expression of hormone-sensitive lipase is reportedly decreased following weight loss programmes [46,47].…”
Section: ±52mentioning
confidence: 99%